PROTEIN AND AMINO ACIDS PROFILE OF LIMA BEAN (PHASEOLUS LUNATUS) FOODS IN KADUNA STATE (FUDMA JOURNAL OF SCIENCES, 2021)
This study was conducted to determine the amino acids content of some lima beans (Phaseolus lunatus) foods in Kaduna State. The foods include lima bean porridge, lima bean-benniseed and lima bean-hungry rice. These foods were subjected to amino acids and proximate analysis using standard procedures and analytical methods. Amino acid composition of lima bean-benniseed recorded higher content of essential amino acids leucine (6.97g/100g), lysine (7.10g/100g), methionine (2.60g/100g), threonine (3.81g/100g), and also had higher content of non-essential amino acids, tyrosine (3.45g/100g), alanine (4.54g/100g), serine (3.94g/100g), glutamic acid (12.94g/100g) and aspartic acid (8.68g/100g). Lima bean-hungryrice food had higher content of isoleucine (4.04g/100g), phenylalanine (4.13g/100g), tryptophan (1.26g/100g). Proximate composition shows that the protein content of lima bean-benniseed food (8.33%) and lima bean porridge (8.30%) were significantly (P
Keywords: Amino acids, Lima bean, Foods, Malnutrition, Proximate